GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2017)
A dataset containing 257472 species occurrences available in GBIF matching the query: TaxonKey: Fagus sylvatica L.. The dataset includes 257472 records from 637 constituent datasets: 1 records from Bioimages. 134 records from Merseyside BioBank (unverified). 1 records from The Vascular Plants Collection of the Regensburgische Botanische Gesellschaft. 6 records from Ektomykorrhizen auf VIP Alb (Wald). 3 records from JOI - Herbário Joinvillea. 2 records from National Trust - Wicken Fen nature reserve species data held by The National Trust. 1 records from Herbarium specimens of the Muséum d'Histoire Naturelle d'Autun (AUT). 64 records from University of British Columbia Herbarium (UBC) - Vascular Plant Collection. 1 records from HUFU - Herbarium Uberlandense. 231 records from Phanerogamic Botanical Collections (S). 7 records from Jordal. 44 records from University of Vienna, Institute for Botany - Herbarium WU. 78 records from Dorset SSSI Species Records 1952 - 2004 (Natural England). 31 records from Vascular Plants, Field notes, Agder naturmuseum (KMN). 259 records from Online Atlas of vascular plants 2012-2020. 343 records from Dorset Sites of Nature Conservation Interest (SNCI) species records pre 2000. 63 records from Bryophytes, fungi and lichens on dead wood. 894 records from Naturalis Biodiversity Center (NL) - Botany Leiden. 5 records from BOTUw - Xiloteca "Profa. Dra. Maria Aparecida Mourão Brasil". 6 records from PlutoF platform observations. 7 records from Herbario Nacional Colombiano (COL). 126 records from EPA River Biologists data. 1 records from Casual records for Scottish Wildlife Trust reserves - Verified data. 32 records from SANT Herbarium vascular plants collection. 2 records from Collection du Musée d'Histoire Naturelle de Nice. 9 records from Local BioBlitz Challenge 2013. 1881 records from FLORIVON. 12525 records from Vascular plants in Denmark recorded under the The Nationwide Monitoring and Assessment Programme for the Aquatic and Terrestrial Environments (NOVANA). 10 records from Karplanter i vernet barskog og edelløvskog. 1 records from University of Alberta Vascular Plant Herbarium (ALTA-VP). 79 records from fundiv france database. 5993 records from Florabank1 - A grid-based database on vascular plant distribution in the northern part of Belgium (Flanders and the Brussels Capital region). 2 records from Digitization of plant specimens from Rhoen and Vogelsberg (FLAD). 272 records from Local Wildlife Site Surveys Berkshire. 8 records from Galls on Beech Trees in Hainich, 2008. 241 records from Phytochorologie des départements français. 6 records from Inventaire National du Patrimoine Naturel : Atlas de la flore de Lorraine. 56 records from BioFokus. 1 records from HUEFS - Herbario da Universidade Estadual de Feira de Santana. 1 records from Bioblitz 2013 Copenhagen Denmark. 1 records from Herbier Louis-Marie (QFA) - Collection de plantes vasculaires. 55 records from Vascular plant herbarium, Agder naturmuseum og botaniske hage. 10 records from CESJ - Herbário Leopoldo Krieger. 41 records from Dutch Foundation for Applied Water Research (STOWA) - Limnodata Neerlandica. 3829 records from Artdata. 4 records from Plant Specimen Database of Tama Forest Science Garden, Forestry and Forest Products Research Institute, Japan. 81 records from BBOWT Local Wildlife Sites Surveys 1994-2003. 10 records from MBM - Herbário do Museu Botânico Municipal. 1 records from Stabbetorp - Floristiske registreringer 2016. 2 records from InboVeg - NICHE-Vlaanderen groundwater related vegetation relevés for Flanders, Belgium. 895 records from Inventaire National du Patrimoine Naturel : Flore du Limousin. 1 records from NCC Berkshire Chalk Grassland Survey 1985. 109 records from OHN. 4712 records from Données ONF Faune-Flore-Fonge. 12 records from Tallinn Botanic Garden. 1 records from Herbarium areqvipense (HUSA). 3 records from Norwegian Biodiversity Information Centre - Other datasets. 31 records from Australia's Virtual Herbarium. 1693 records from Fundación Biodiversidad, Real Jardín Botánico (CSIC): Anthos. Sistema de Información de las plantas de España. 40 records from Herbier de Strasbourg. 87 records from Vascular Plant Herbarium, UiB. 2 records from Kathryn Kalmbach Herbarium. 406 records from Hertfordshire Natural History Society Flora Group - Hertfordshire Flora Survey Records 1987-2005. 21 records from Natural History Museum Maastricht (NL) - Herbarium. 118 records from iNaturalist Research-grade Observations. 1 records from UCBG TAPIR Provider. 9 records from CONN. 2 records from HUCS - Herbário da Universidade de Caxias do Sul. 1 records from H.A. Stephens Herbarium. 164 records from Merseyside BioBank Active Naturalists (unverified). 1 records from University of Lethbridge Herbarium (LEA). 9 records from Estonian Museum of Natural History. 1 records from Collection botanique Le Grand A. (BOUM). 8 records from NINA botanical collection. 21 records from Estonian University of Life Sciences. 186 records from A common plants survey of vascular plants in South Northumberland and Durham, United Kingdom. 17 records from Herbarium of the Department of Natural Forests (Forest Research Institute). 1 records from Klasse 3a. 1 records from Küstenschutzwald. 1 records from Kremmer Luch. 1 records from Feriendorf Ober-Seemen. 1 records from Förderzentrum Schmölln. 1 records from Kloster Eberbach. 1 records from Ehmkendorf. 1 records from Isarufer. 1 records from Waldsee. 1 records from Feriendorf des Kreises Gedern (Ober-Seemen). 1 records from Hainhoop - Tonkuhle - Bullenmoor (Arpke). 1 records from Dierloch, nördlicher Mooswald (Freiburg-Hochdorf). 1 records from Herbarium specimens of Association des Naturalistes de la vallée du Loing (ANVL). 1 records from Berlin - Treptower Park / Karpfenteich. 1 records from "Schlechteberg" Ebersbach/Sa.. 1 records from Kinder- und Jugendferiendorf des Kreises Groß-Gerau - Gedern/Ober-Seemen. 1 records from Fuchsloch (Mohlsdorf/Ostthüringen). 1 records from Lassentiner Moor (Niepars). 1 records from Schulgarten mit Klasse 8a (Essen). 1 records from Döchtbühlwald (Bad Waldsee). 1 records from Roter Berg Werdau (Leubnitz). 1 records from Waldhusener Moor (Lübeck-Kücknitz). 1 records from AKG-Bensheim. 1 records from Artenvielfalt Kreis Gießen. 1 records from Alter Nördlicher Friedhof (München). 1 records from Schulgelände Gebrüder-Grimm-Schuleund Umgebung (Lingen). 1 records from Südpark (Bochum-Wattenscheid). 1 records from Flusswerder in der Weser (Hameln). 1 records from Wedeler Au. 1 records from Bodenseeufer Radolfzell. 1 records from Triebesbach (Zeulenroda-Triebes). 1 records from Ortelsbruch - Hangmoor bei Morbach. 1 records from "Schwarzes Teich" (Waldpark Radebeul). 1 records from Lillachtal mit Kalktuffquelle bei Weißenohe. 1 records from "Ach, du dicke Eiche", Wald an der Oste-Grundschule Heeslingen. 2 records from Schulgelände Paul-Gerhardt-Schule-Dassel. 1 records from Örtzemündung (Stedden). 1 records from Wangerooge. 1 records from Steinbruch Mainz-Weisenau, 2. Jahr. 1322 records from Fungus Collections at Staatliches Museum für Naturkunde Karlsruhe (Herbarium KR). 1 records from Wirbach. 1 records from Geschützter Landschaftsbestandteil - GLB "Troppach". 1 records from Paul-Gerhardt-Schule Dassel. 1 records from privater Garten. 1 records from Westerwälder Umwelt- und Naturschutztag Limesgemeinde Hillscheid. 1 records from CommunicA Koblenz - Wildkräuterexkursion - Rheinsteig Bornhofer Höhe. 1 records from Alter Kreidebruch Saßnitz/Rügen. 1 records from Natur erleben rund um den Seminarbauernhof Gut Hohenberg. 1 records from Rund um das LUGY. 1 records from Insektenvielfalt Ahe/Weichelsee. 1 records from Ludwigshofen. 2 records from Landschaftsschutzgebiet Buchhorst 3. 1 records from Bolzplatz. 1 records from Spielwiese. 1 records from Kindergarten. 1 records from Wassermann. 1 records from GymnQuerfurt. 1 records from Brander Wald (Stolberg). 1 records from Balkon (Norderstedt). 1 records from Garten J. Scherrer (Lachen-Speyerdorf). 1 records from NABU VG Weilerbach - NSG Mehlinger Heide, FFH-Gebiet. 1 records from Schulhof der Astrid-Lindgren-Schule Elmshorn. 1 records from Naturparadies in Gräfenhausen am Trifels (bei Annweiler). 1 records from Rückkehr der Biber in Rheinland-Pfalz - Biber in der Primmerbach. 1 records from WildesMoor bei Schwabstedt. 1 records from Isartal Dingolfing. 2 records from Dalbekschlucht. 1 records from Höltigbaum. 1 records from Waldstück Bremerhagen LK Bio Kl. 12. 1 records from Gelände des Schulzentrums am Himmelsbarg. 1 records from Biosphäre Bliesgau. 1 records from Wulfsmuehle/Pinnau. 1 records from Industriebrache (Kempen). 1 records from Kurler Busch (Scharnhorst). 2 records from Römertal (Steinpleis). 2 records from Klütwald. 1 records from Gym Freyung. 1 records from Hoher Stein Kallenhardt. 1 records from Mühlenbach bei Buxtehude. 1 records from Schulgarten-St.-Georg-Gymnasium. 1 records from Mauervegetation,Flechten und anderes. 1 records from Sudeniederung (Amt Neuhaus). 31 records from IBF Monitoring of Plant Galls. 1 records from Tiere und Pflanzen um uns herum !. 1 records from Landschaftsschutzgebiet Buchhorst 4. 1 records from Schulinnenhöfe (Gelsenkirchen). 1 records from Innenhöfe der Gesamtschule Berger Feld/ Gelsenkirchen. 1 records from Tiere und Pflanzen am Pfannenbach. 1 records from FFH-Gebiet "Calwer Heckengäu". 1 records from Landschaftsschutzgebiet Schmutterwald. 1 records from Schwanner Warte / Kinderhaus St. Elisabeth Waldplatz. 2 records from GEO-Hauptveranstaltung im Nationalpark Bayerischer Wald. 1 records from Bannwald Burghauser Forst. 1 records from Waldfläche im Natur-Erlebnis-Pfad Pfinztal. 1 records from 10. GEO - Tag der Artenvielfalt 2008 - LSG "Pfarrhübel" Chemnitz. 1 records from Rohrmeistereiplateau und angrenzendes Gebiet. 1 records from Fürstenberger Ralley Teil 3. 1 records from Artenvielfalt in der Stadt: Botanischer Garten Wuppertal und Hardt. 1 records from Natur-Erlebnisgebiet der Naturschutz-Akademie Hessen und Umgebung. 1 records from Pöhlberg bei Annaberg. 1 records from Expedition "Schulgelände". 1 records from Biosphärenpark Wienerwald - Wiener Steinhofgründe. 2 records from Schulzentrum "Parc Hosingen". 1 records from LK 11 im Mönchspark. 1 records from Schulwald Grundschule Brügge. 1 records from Weinberg Reichersdorf. 1 records from Schulwald Marksuhl. 1 records from Tag der Artenvielfalt in Heidelberg. 1 records from Gronau - auf der Suche nach dem Neunauge. 2 records from Langes Tannen(LMS), Klasse 5d. 1 records from Liether Park 2 (LMS), Klasse 6c. 1 records from Königsdorfer Wald. 1 records from Wiesen-Wälder-Wasser um Dansenberg, Biosphärenreservat Pfälzerwald. 1 records from Streuobstwiese Stedar. 1 records from VFD-H: Heidenrod: Beckers Weide mit Wald. 1 records from Feldweg Waldkirchen. 1 records from Aachtobel. 1 records from Artenvielfalt im Naturschutzgebiet an der Loreley - Leiselfeld/Spitznack - 2. Jahr. 1 records from Wälder im Hainbachtal. 1 records from Rund um den Hainbergsee. 1 records from Pflanzen und Tiere im Burgwald. 1 records from Wir erkunden die Hofau, Klasse 5c. 1 records from Von der Nutzung zur Natur. 1 records from Liether Park 1 (LMS), Klasse 5b. 1 records from Landschaftsschutzgebiet Buchhorst2. 1 records from Sonntagmorgen-Veranstaltungen im Zeichen des GEO-Tags. 1 records from VFD HH/SH "Pferdeweide Lemsahl". 1 records from Rosarium (LMS), Klasse 6a. 1 records from Reusaer Wald. 1 records from Rechts des Inn Höhe Hofau Rosenheim. 1 records from Höhle am Neuweg / Sächsische Schweiz. 1 records from "Schwarzwassertal" bei Pobershau. 8910 records from Occurrence Data of Vascular Plants collected or compiled for the Flora of Bavaria. 2 records from Naturalis Biodiversity Center (NL) - Micropaleontology. 3 records from TestWat - Macroinvertebrates and macrophytes of freshwater bodies in Flanders, Belgium. 5 records from Ektomykorrhizen auf VIP Schorfheide (Wald). 2 records from OAC-BIO Herbarium. 208 records from Naturhistorisches Museum Mainz, Feldbeobachtungsdaten Pflanzen. 2829 records from naturgucker. 5 records from English Nature Oxfordshire Chalk Grassland Survey. 9 records from RHS monitoring of native and naturalised plants and animals at its gardens and surrounding areas. 8 records from National Trust - Hatfield Forest species data held by The National Trust.. 1 records from Scottish Natural Heritage - Standing Waters Database. 1 records from English Nature Oxford City Surveys. 2 records from Freiburger GEO-Tag der Artenvielfalt. 1 records from Sandloch - Höhle. 1 records from Biosphärenpark Wienerwald - Pfaffstätten. 1 records from Kühmark bei Wetzlar. 1 records from Eschlberg Thalhausen. 1 records from GEO-Hauptveranstaltung in "Wildtierland". 1 records from Sahrbachtal Kreis Ahrweiler. 1 records from Schulgelände des Schulzentrums am Himmelsbarg. 1 records from Baggerseen bei Krauchenwies. 1 records from Schriesheimer Steinbruch. 1 records from Artenvielfalt in der Kinderakademie im RFZ. 1 records from Artenerfassung für Jedermann in der Grundschule Kirchboitzen. 1 records from Mangfalltal. 1 records from LBV 100 - Artenvielfalt am Rothsee. 1 records from Naturpark Kottenforst-Ville 18.6.09. 1 records from Naturpark Kottenforst-Ville Sammelaktion 15.-19.6.. 1 records from Aktion - Friedensburg Oberschule. 1 records from Artenvielfalt im Rhein-Neckar-Raum. 1 records from 6. Tag der Artenvielfalt Hockenheim Thema: Wald 12.-14.6.2009. 2 records from Biotope in Rheine - Aktion 350. 1 records from Artenvielfalt am "Grünen Band" bei Coburg: 20 Jahre Wiedervereinigung. 1 records from Von Elf bis Elf" Der Botanische Garten Wuppertal. 1 records from Die Teiche im Britzer Garten. 1 records from Naturpark Kottenforst-Ville 15.6.09. 2 records from Liether Park (LMS), 6g. 1 records from Nationalpark Jasmund. 1 records from Bulau. 1 records from Werl macht sich auf die Suche. 1 records from Feuchtbiotop Weidenkaule. 1 records from Mönchspark. 1 records from Wälder bei Nordkirchen. 1 records from BB-Biodiversität b. 1 records from Naturpark Kottenforst-Ville 19.6.09. 1 records from Freiburger GEO-Tag der Artenvielfalt am Moosweiher in Freiburg und im angrenzenden Mooswald. 1 records from Bayerische Donau - Blindheim Donaubrücke. 1 records from Streuobstwiese Stedar 2008. 1 records from Schloss Fasanerie Eichenzell. 1 records from Streuobstwiese Stedar 2009. 1 records from Feuchtwiese in Langes Tannen (LMS), Klasse 5c. 1 records from Liether Park (LMS), 5a. 1 records from Liether Park (LMS), 6c. 1 records from Liether Park (LMS), 6b. 1 records from Schiller Gymnasium Hof 10b. 1 records from Einen Tag lang Forscher sein - Die 5c der Erich-Kästner-Schule erforscht das Bachemer Wiesental. 1 records from Lebensraum Walram. 1 records from Artenvielfalt des "Grünen Klassenzimmers". 1 records from Laubmischwald bei der Internationalen Grundschule Potsdam. 1 records from Naturpark Sternberger Seenland. 1 records from Biotope entdecken im Kockmecker Siepen (Sauerland). 1 records from Listhof und Umgebung. 1 records from Naturpark Kottenforst-Ville 16.6.09. 1 records from Naturpark Kottenforst-Ville 17.6.09. 1 records from Raus in die Natur. 1 records from Rund ums Schulgelände. 1 records from Naturschutzgebiet Lüneburger Heide. 3 records from Plant Specimens collections of the Kyushu UNniversity Museum. 31 records from Fragment size of individual Fagus sylvatica trees based on microsatellite markers. 23328 records from Dutch Vegetation Database (LVD). 66652 records from INPN - Données flore des CBN agrégées par la FCBN. 1 records from EFC - Herbário Escola de Florestas Curitiba. 3152 records from The Fungal Collection at the Senckenberg Museum für Naturkunde Görlitz. 1 records from CeDoc de Biodiversitat Vegetal: BCN-Seeds. 1 records from Cuxhaven Schlosspark, Klasse 5e- Amandus-Abendroth-Gymnasium. 22 records from Jardin botanique de Montréal (JBM). 1 records from Feuchtbiotop Otto-Hahn-Gymnasium. 1 records from Fliegenhaupt Marksuhl. 213 records from Dorset Sites of Nature Conservation Interest (SNCI) species records 2000-2008. 1 records from Flora und Fauna im Brexbachtal. 1 records from Grünes Germersheim. 1 records from Kindervilla Aussengelände/ Hiltroper Park. 1 records from Neißetal. 1 records from Sukzession Industriebrache. 1 records from TBW-Schafberg. 66 records from Royal Botanic Garden Edinburgh Living Plant Collections (E). 1035 records from Tiroler Landesmuseum Ferdinandeum. 22 records from The Fungal Collection at the Botanische Staatssammlung München. 1572 records from IBF Monitoring of Vascular Plants. 11 records from IBF Monitoring of Lichens. 30 records from IBF Monitoring of Fungi. 31 records from The Lichen Collection at the Botanische Staatssammlung München. 20 records from The Exsiccatal Series "Triebel, Microfungi exsiccati". 2250 records from The Fungal and Lichen Collections at the Herbarium Marburgense. 11 records from Tropicos Specimen Data. 12 records from Nature Conservancy Council Berkshire Meadows Survey 1984-87 (as held by Thames Valley Environmental Records Centre). 1643 records from BRERC species records recorded over 15 years ago. 13 records from Natural History Museum (London) Collection Specimens. 207 records from Catálogo Florístico Histórico de Navarra. Gobierno de Navarra. 1 records from Fundación Carl Faust: Herbario del Jardí Botànic Marimurtra: HMIM. 19 records from Natural History Museum, Vienna - Herbarium W. 10 records from Computarización de la xiloteca Dr. Faustino Miranda del Instituto de Ecología, AC. 126 records from Ireland's BioBlitz. 215 records from Karl Franzens University of Graz, Insitute for Botany - Herbarium GZU. 2 records from Colección científica del Museo de Historia Natural Alfredo Dugés. 10 records from Base de datos para la xiloteca del Instituto de Biología de la UNAM. 230 records from Dataflos. 15 records from Leiner-Herbar Konstanz. 24 records from NMNH Extant Specimen and Observation Records. 1 records from Universität Salzburg. 687 records from The Fungal Collection of Helga Große-Brauckmann at the Botanische Staatssammlung München. 21 records from Botanical Garden Collection. 37 records from Colección de plantas vasculares del herbario de la Universitat de València (VAL).. 35 records from Herbario de Plantas Vasculares de la Universidad de Salamanca: SALA. 169 records from Real Jardín Botánico (Madrid), Vascular Plant Herbarium (MA). 15 records from Universidad de Oviedo. Departamento de Biología de Organismos y Sistemas: FCO. 20 records from Jardín Botánico de Córdoba: Herbarium COA. 27 records from Aranzadi Zientzi Elkartea. 5 records from CIBIO, Alicante:ABH-GBIF. 1 records from Herbarium of Vascular Plants Collection of the University of Extremadura (Spain). 38 records from Herbario EMMA. Herbario de la Escuela Técnica Superior de Ingenieros de Montes. UPM. 25 records from Herbario de la Universidad de Sevilla. 3 records from Herbario de la Universidad de Sevilla, SEV-Historico. 16 records from Herbario HSS Finca La Orden-Valdesequera (CICYTEX). Gobierno de Extremadura. 3 records from Dpto de Botánica, Ecología y Fisiología Vegetal (Herbario COFC). Facultad de Ciencias. Universidad de Córdoba. 9 records from Institut Botanic de Barcelona, BC. 1 records from Hortus Botanicus Sollerensis Herbarium (FBonafè). 13 records from Auckland Museum Botany Collection. 6 records from Botanic Garden of the Finnish Museum of Natural History. 48 records from University of Copenhagen Arboretum. 23 records from Botany registration database by Danish botanists. 1 records from Flora exsiccata Bavarica. 1 records from GEO Biodiversity Day. 15 records from Herbarium Berolinense. 2 records from Herbarium Willing. 18 records from Staatliches Museum für Naturkunde Stuttgart, Herbarium. 13151 records from Observations du Conservatoire botanique national du Bassin parisien.. 90 records from Biologiezentrum Linz. 13 records from Herbarium Senckenbergianum Görlitz (GLM). 1 records from United States National Plant Germplasm System Collection. 1 records from Epiphytic Lichens of G. Lettau at the Botanical Museum Berlin-Dahlem. 4 records from The Collection of Lichenicolous Fungi at the Botanische Staatssammlung München. 23 records from The Erysiphales Collection at the Botanische Staatssammlung München. 2 records from The Erysiphales Collection at the University Halle-Wittenberg. 1 records from The Myxomycetes Collections at the Botanische Staatssammlung München - Main Collection. 6 records from Water Colours of Fungi by Konrad Schieferdecker at the Botanische Staatssammlung München. 1794 records from Floristische Kartierung Österreichs - Mapping the Flora of Austria. 3 records from Universidad Politécnica de Madrid, Dpto. Biología Vegetal, Banco de Germoplasma. 3 records from Institut Botanic de Barcelona, BC-Histórico. 6 records from Harvard University Herbaria. 2 records from Herbarium BSG Vascular Plants. 15 records from inatura - Erlebnis Naturschau Dornbirn. 4 records from EURISCO, The European Genetic Resources Search Catalogue. 8 records from Central Scotland Forest Trust - South Lanarkshire peatland records 2013. 60 records from Plant specimens depodited in Osaka Museum of Natural History, Japan.. 1116 records from Staffordshire Ecological Record - SER Site-based Surveys. 54 records from Biodiversitätsdatenbank des Landes Salzburg. 2 records from English Nature Berkshire SSSI Records. 254 records from Commissioned surveys and staff surveys and reports for Scottish Wildlife Trust reserves - Verified data. 1 records from Vascular Plants, Observations, Oslo (O). 1157 records from FloVegSI - Floristical and fitocenological database of ZRC SAZU. 1 records from BÜG. 1 records from LaBoOb02. 1 records from Klutensee. 1 records from Überall ist Wunderland. 1 records from DJH. 1 records from Am Moosangerweg. 1 records from Frau Voss. 1 records from Danielsberg (Mölltal, Kärnten). 1 records from Naturschutzgebiet Sistig-Krekeler-Heide. 1 records from AKG-Gelände (Bensheim). 1 records from FFH-Gebiet Ahrbachtal. 1 records from Botanischer Garten (Saarbrücken). 1 records from Trockenhang Greinhartsberg Edelfingen. 1 records from GEO-Hauptveranstaltung (NLP Harz / Hochharz). 1 records from Hamberger Brücke / Würmtal (Pforzheim). 2 records from Waldränder der Frankenhöhe (Rothenburg ob der Tauber). 1 records from Sandhofen. 2 records from Kernberge und Umgebung (Jena). 1 records from Schlichemquelle (Tieringen/Meßstetten). 1 records from Mooswald (Freiburg). 1 records from Gemeinde Sursee. 1 records from Gewann Krampf (Heilbronn). 1 records from Naturschutzstation Schmidsfelden. 1 records from Naturschutzgebiet Bausenberg. 1 records from Langenberger Forst am Ochsenweg/ Niebüll-Leck. 1 records from GEO Hauptveranstaltung Tirol (Innsbruck). 1 records from Schulgelände IGS Kaufungen. 2 records from Schule Sulzbach (Oberegg). 1 records from Zukünftiges NSG Höftland/Bockholmwik. 1 records from Königstetten. 1 records from Frauenholz (Holzmaden). 1 records from Freiburger Tag der Artenvielfalt. 1 records from Erzental (Oberotterbach). 1 records from Langes Tannen (Uetersen). 1 records from Stausee (Oberdigisheim/Meßstetten). 1 records from Erlengraben/Lipp-Tal (Östringen). 1 records from Wald und Wiese am Buchwald. 4 records from Silbertor + Wasserbachtal (Rutesheim / Renningen). 1 records from NSG Karwendel. 1 records from NSG Hülenbuch Hörnle (Tieringen/Meßstetten). 1 records from Neckartalsüdhang (Horb). 2 records from Umgebung der Gesamtschule Hamburg-Winterhude. 1 records from Langes Tannen. 2 records from Rund um den Eichwald,Schulhof Friedrich Fröbel Gymnasium- Bad Blankenburg. 1 records from Sonnentaugemeinschaft. 1 records from Schulgelände IGS-Frosch (Thaleischweiler-Fröschen). 1 records from Philosophenwald und Wieseckaue in Gießen. 1 records from Artenvielfalt auf Restbauernhof. 1 records from Wiese und Weide am Waldrand von Gusterath. 1 records from Blumenrather Heide / Virneburg. 1 records from Cuxhavener Küstenheiden. 1 records from Umgebung von Schorndorf. 1 records from Artenvielfalt auf der Weide - GEO-Hauptveranstaltung in Crawinkel. 1 records from katzenbuckel. 1 records from Promberg1. 1 records from GEO-Hauptveranstaltung (Insel Vilm). 1 records from GEO-Hauptveranstaltung (Duisburg). 1 records from Wanderweg am Windebyer Noor (bei Eckernförde). 1 records from BUND - Dassower See (Lübeck/Dassow). 1 records from Wildes Bremer Leben im Park. 1 records from Naturschutzgebiet Heiliger Hain (Wahrenholz). 1 records from Sudeniederung (Amt Neuhaus), Landkreis Lüneburg. 1 records from Stadtbiotop Ulrichteich. 1 records from Artenfülle um das Schalkenmehrener Maar. 2 records from Trockenrasen und Buchenwald in der Umgebung der Jugendherberge Bad Blankenburg. 1 records from KARSTLANDSCHAFT SÜDHARZ - VOM GIPSABBAU BEDROHT (Grenzstreifen am Röseberg). 1 records from 20 Jahre Naturschutzgebiet Dreienberg. 1 records from Biotope auf dem Gelände der Eggerstedt- Kaserne in der Nachbarschaft der Theodor-Heuss-Schule. 1 records from Pottundkopp. 1 records from Knechtweide (Kohlfurth). 1 records from Wald am Schloss Wittgenstein Bad Laasphe. 2 records from Ökostation (Freiburg). 1 records from Langes Tannen in Uetersen. 1 records from Außenfeuerstelle Königsbol (Hartheim/Meßstetten). 1 records from Landschaftsschutzgebiet Hexenberg (Erftstadt-Erp). 1 records from Schulhof Gymnasium Hürth Bonnstrasse. 1 records from NABU Naturschutzhof Netttetal (Sassenfeld) e.V.. 1 records from NSG Berschau - Auengebiet (Neustadt / Wied). 1 records from Gemeindegebiet Weikendorf (Marchfeld). 1 records from Umgebung der Gesamtschule Winterhude (Hamburg). 1 records from Lebensraum Gesamtschule (Langerwehe). 1 records from Tiergarten (Zeitz). 2 records from Schloß Türnich (Kerpen). 1 records from Unser Schulhof - eine Apotheke. 1 records from Quarrendorfer Landschaftsschutzgebiet. 1 records from Faberpark (Nürnberg/Stein). 1 records from Unser Schulhof. 2 records from Umgebung der Elsa-Brändström-Schule (Krückaupark). 1 records from Streuobstwiese Kugelberg (Ulm). 1 records from Wiese am Waldrand (Gurtweil). 1 records from Urwald 1 (Bad Waldsee). 1 records from Fuldaaue (Stadtgebiet Fulda). 1 records from Stadtgebiet (Dannenberg). 1 records from Orchideenstandort Nostengraben - Kretzberg (Oßmaritz). 2 records from Renaturierung Werse (Innenbereich Beckum). 1 records from Naturschutzgebiete um das Christliche-Spalatin-Gymnasium Altenburg. 1 records from Bergkamen- Bergehalde Großes Holz. 1 records from Lüner Holz (Lüneburg). 2 records from Stadt Königs Wusterhausen. 2 records from Stadtpark Sulzbach-Rosenberg. 1 records from Lindau im Bodensee. 1 records from Schulgelände Dientzenhofer-Gymnasium (Bamberg). 2 records from Feriendorf des Kreises Groß-Gerau Ober-Seemen/Gedern. 1 records from Schulhof und Anlagensee in Nellingen. 1 records from Unser kleines Rasenstück/ Dürer-Gymnasium Nürnberg. 1 records from Werremündung im Schwarzatal. 1 records from Klimaoasen in Köln. 1 records from Schlattstaller Tal (Lenningen). 5 records from Eppingen und Umgebung. 1 records from Steinbruch Haas Stuttgart-Münster. 1 records from Hemmerder Schelk (Unna). 1 records from NABU-Projekt (Osterode am Harz) Südharzer Gipskarst. 1 records from renaturierter Main (Kemmern bei Bamberg). 1 records from Prophetensee Quickborn. 2 records from Lebensraum Stadt und Park. 1 records from Wupperaue bei Kemna (Wuppertal). 1 records from Dreilinden Gymnasium-Schulgelände. 1 records from Altenburg bei Bamberg. 4 records from Naturerlebnisraum Koppelsberg. 1 records from GNOR-Projekt "Halbwilde Weidehaltung zwischen Kamp-Bornhofen und Kestert" und Umland. 1 records from Walldorf-Wiesloch: "Natur über den Gleisen". 1 records from Mißmahlsche Anlage. 2 records from Naturgarten Langenholtensen. 1 records from VSN-Wiese. 1 records from Arteninventar rund um den Rannahof. 2 records from Tag der Artenvielfalt. 1 records from Artenvielfalt auf dem Schulgelände. 4 records from Feriendorf des Kreises Groß-Gerau/Ober-Seemen. 1 records from Unna-Mühlhausen, Wiesen. 1 records from USF Herbarium. 6 records from Plantae, TAIF (Taiwan e-Learning and Digital Archives Program, TELDAP). 1569 records from Atlas Flora Danica. 12 records from Natural History Museum, University of Tartu. 447 records from Base de datos de plantas vasculares del País Vasco: ARAN-EH. 12 records from Field Museum of Natural History (Botany) Seed Plant Collection. 8 records from MPM Milwaukee Public Museum Herbarium. 2112 records from Belgian IFBL Flora Checklists (1939-1971). 5105 records from Inventaire National du Patrimoine Naturel : Flore Franco-Belge. 1 records from Perchtoldsdorfer Heide. 1 records from Naturpark Drömling. 1 records from Schwanheimer Wald. 1 records from Freiburger Netzwerk Artenvielfalt. 1 records from Tage der Artenvielfalt rund um die Naturschutzstation Molsberg. 1 records from Halbwilde Weidehaltung zwischen Kamp-Bornhofen und Kestert sowie Umland. 1 records from Tag der Artenvielfalt mit SchülerInnen des Europa-Gymnasiums in Wörth am Rhein. 1 records from NSG Dellwiger Wald, Dortmund. 1 records from Töpinger Mischwald. 1 records from Waldstück am Schullandheim Bad Bederkesa. 1 records from Lustadter Wald .. 1 records from Kohlstattbrunnental. 3 records from EDIT - ATBI in Gemer area (Slovakia). 7 records from Banco de Datos de la Biodiversidad de la Comunitat Valenciana. 2 records from Herbario de la Universidad Pública de Navarra, Pamplona: UPNA-H. 1 records from Vom Gipfel ins Moor, Transekt im NSG Allgäuer Hochalpen. 1 records from VFD-BW, Linzgau: Pferdeweiden Neuweiler Hof. 2 records from Jardín Botánico Atlántico, Gijón: JBAG-Laínz. 14 records from MGC Herbarium of University of Malaga (Spain): MGC-Cormof dataset. 1287 records from Biological and palaeontological collection and observation data MNHNL. 7 records from Botany Division, Yale Peabody Museum. 1 records from Tag der Artenvielfalt im Taubental. 25 records from Herbarium Senckenbergianum (FR). 10 records from Universidad de Oviedo. Departamento de Biología de Organismos y Sistemas: FCO-Briof. 1 records from Herbario de Universidad de Murcia: MUB. 4 records from Herbarium of Taiwan Forestry Research Institute. 9 records from Herbarium specimens of the Muséum d'Histoire Naturelle of Aix-en-Provence (AIX). 10 records from TransForest vegetation data. 1 records from National Trust - Anglesey Abbey wildlife species data held by The National Trust.. 49 records from VIT Herbarium - Vascular Plants (The Natural History Museum of Alava). 2 records from Vascular Herbarium, NMBU. 6 records from Wetland Inventory (NV). 2851 records from The DNA and Sample Repository at AIT. 1648 records from FloraCAT: Banco de datos de los cormófitos de Cataluña. 4 records from National Trust - Sutton Hoo species data held by The National Trust.. 4 records from UPCB - Herbário do Departamento de Botânica. 2 records from Herbarium specimens, Harmas J.H. Fabre (FABR - Sérignan-du-Comtat) of the Muséum national d'Histoire naturelle (MNHN - Paris). 2 records from Faun. 36 records from Heritage Trees of Ireland. 1 records from Flora d'Andorra. 7 records from Survey and monitoring records for Scottish Wildlife Trust reserves from reserve convenors and Trust volunteers - Verified data. 23 records from National System of Protected Areas in Poland - Plants. 8 records from ArtenFinder. 67 records from Lund Botanical Museum (LD). 4 records from vegetation releves on grassland gridplots 2007-2009. 35 records from National Trust - Ickworth species data held by The National Trust.. 14901 records from VegetWeb - Repositorium von Vegetationsaufnahmen a. 2 records from Geographically tagged INSDC sequences. 2 records from 2000-2003 RBWM WHS Surveys. 6 records from vegetation releves on grassland gridplots in 2007. 1 records from Royal Museum of Central Africa - Metafro-Infosys - Xylarium. 579 records from Norwegian Species Observation Service. 2 records from The fossil collection (F) of the Muséum national d'Histoire naturelle (MNHN - Paris). 20 records from Merseyside BioBank Active Naturalists (verified). 3 records from Vascular Plants, Museum of Archaeology, University of Stavanger. 376 records from The vascular plants collection (P) at the Herbarium of the Muséum national d'Histoire Naturelle (MNHN - Paris). 16 records from SBT-Living. 34 records from Fauna and flora inventories (terrestrial and limnetic) from the South of Belgium. 397 records from Carnet en Ligne. 77 records from Staffordshire Ecological Record - SER Species-based Surveys. 1 records from Herbario IES San Isidoro de Sevilla. 1 records from CEPEC - Herbário do Centro de Pesquisas do Cacau. 31 records from Royal Botanic Garden Edinburgh Herbarium (E). 1 records from Inventaire National du Patrimoine Naturel : Espèces Végétales Menacées de France métropolitaine. 1218 records from Waarnemingen.be - Plant occurrences in Flanders and the Brussels Capital Region, Belgium. 37 records from Botany (UPS). 41 records from LNHG Biological Records Dataset. 965 records from Merseyside BioBank (verified). 519 records from National Forest Inventory (SLU). 3 records from University of British Columbia Botanical Garden Collections (UBCBG). 41 records from SMNS Palaeontological collection - Fossil plants. 2982 records from Vascular plant diversity in forests. 810 records from Inventaire National du Patrimoine Naturel : Flore d'Ille-et-Vilaine. 18 records from Ektomykorrhizen auf VIP Hainich (Wald). 9 records from Herbarium specimens of Université de Montpellier 2, Institut de Botanique (MPU)). 4 records from ESA - Herbário da Escola Superior de Agricultura Luiz de Queiroz. 1 records from Royal Botanic Gardens, Kew - Herbarium Specimens. 60 records from Countryside Council for Wales - Welsh Invertebrate Database (WID). 14 records from Vascular plant herbarium, Tromsø Museum. 1 records from MPUC - Herbário do Museu da Pontifícia Universidade Católica do Rio Grande do Sul. 61 records from Vascular plant herbarium, NTNU University Museum. 4712 records from Données ONF Faune-Flore-FOnge. 3 records from New Zealand Biodiversity Recording Network. 97 records from Vascular Plants, Field notes, Oslo (O). 11 records from The New York Botanical Garden Herbarium (NY) - Vascular Plant Collection. 3759 records from Sistema de Información de la vegetación Ibérica y Macaronésica. 910 records from Vegetation data from protected areas in Denmark (§ 3 in the Danish Nature Protection Act). 11 records from Universidad de Navarra, Herbarium: PAMP-Vascular Plants. 1 records from Green Plant Herbarium (TRT). 638 records from Inventaire National du Patrimoine Naturel : Flore du Massif Armoricain. 15 records from Miscellaneous Vascular Plants. 2 records from Gothenburg Herbarium - General (GBIF:IH:GB:Herbarium). 971 records from Floristic Databases of Mecklenburg-Pomerania - Higher Plants. 9 records from Allan Herbarium (CHR). 144 records from SysTax - Botanical Gardens. 2 records from Herbarium of University of Białystok - Vascular Plants. 438 records from Flore de Franche-Comté. 2 records from BioFresh Pond Data. 1 records from HPL - Herbário do Jardim Botânico Plantarum. 7 records from BoBO - Botanic Garden and Botanical Museum Berlin-Dahlem Observations. 241 records from Nature Conservancy Council Survey of Ancient Woodlands in Berkshire.. 14 records from Digitization of plant specimens from Rhoen and Vogelsberg (FULD). 239 records from Vascular Plant Herbarium, Oslo (O). 2 records from The Bergius Herbarium. 6 records from Herbarium specimens of Jardins botaniques and Conservatoire Botanique of Nancy (NCY). 210 records from Local Wildlife Site Surveys Oxfordshire. 14 records from Anymals+plants - Citizen Science Data. 12 records from Natural History Museum Rotterdam (NL) - Plantae collection. 22148 records from Flora von Deutschland (Phanerogamen). 4 records from Vascular plants of Amrum 2007-2008. 1348 records from Suffolk Biodiversity Information Service (SBIS) Dataset. 2 records from E. C. Smith Herbarium (ACAD). 1 records from Herbario de Plantas Vasculares de la Asociación BIGA para el estudio del patrimonio natural de Galicia: FBIGA. 115 records from National Trust for Scotland Species Records. 2 records from Actualización de las bases de datos de colecciones, especies en peligro de extinción, colecta y propagación de germoplasma. 10 records from Vascular plant field notes, NTNU University Museum. 13 records from SysTax - Herbaria. 1 records from IPA - Herbário - IPA Dárdano de Andrade Lima. 8 records from Geneva Herbarium – General Collection (G). 3 records from English Nature and NCC Oxfordshire Surveys. 2 records from Nijmegen Natural History Museum (NL) - Herbarium. 2240 records from Institute of Dendrology PAS, Flora of Sudety Mountains. 840 records from BRERC species records within last 15 years. 532 records from Flora of the Stołowe Mts.. 4878 records from Atlas des plantes vasculaires de Lorraine. 4488 records from Tercer Inventario Forestal Nacional. Ministerio de Agricultura, Alimentación y Medio Ambiente (España/Spain). 3 records from 2003-2004 Wokingham WHS Surveys. 6 records from NCC Berkshire Grassland Survey 1984-1987. 5 records from PACA-AGP - Herbarium Anchieta. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences